Association of food consumption patterns and physical activity with obesity among junior high school students in Tangerang, Indonesia: A cross-sectional study - Riswahyuni Widhawati; Beata Rivani; Syifaa Budi Nurazizah (Indonesian Journal of Health Services, 2026)
Background: Adolescent obesity has become an increasing global public health concern due to its association with unhealthy dietary behaviors and insufficient physical activity. Changes in food consumption patterns, particularly the frequent intake of energy-dense fast foods, along with sedentary lifestyles, contribute significantly to the rising prevalence of obesity among school-aged populations. Objective: This study aimed to examine the association between food consumption patterns and physical activity with obesity among junior high school students. Methods: A quantitative analytical study with a cross-sectional design was conducted among 70 eighth-grade students at a junior high school in Tangerang City, Indonesia. Participants were selected using simple random sampling. Food consumption patterns were assessed using a Food Frequency Questionnaire (FFQ), physical activity was measured using the International Physical Activity Questionnaire (IPAQ), and obesity status was determined based on Body Mass Index (BMI). Data were analyzed using descriptive statistics and Chi-square tests to identify associations between variables, with Odds Ratios calculated to estimate risk magnitude. Results: More than half of respondents were categorized as obese. Habitual junk food consumption was reported by the majority of students, and most participants demonstrated low levels of physical activity. Significant associations were identified between junk food consumption and obesity (p < 0.001; OR = 42.095) and between physical activity level and obesity (p < 0.001; OR = 133.714). Students with habitual junk food consumption and poor physical activity levels showed substantially higher odds of obesity. Conclusion: Unhealthy food consumption patterns and insufficient physical activity are strongly associated with obesity among junior high school students. Integrated school-based interventions focusing on nutritional education and physical activity promotion are essential to reduce obesity prevalence in adolescent populations.